2020
DOI: 10.1007/s00330-020-06835-4
|View full text |Cite
|
Sign up to set email alerts
|

MRI features and texture analysis for the early prediction of therapeutic response to neoadjuvant chemoradiotherapy and tumor recurrence of locally advanced rectal cancer

Abstract: Objectives This study aimed to evaluate the efficiency of imaging features and texture analysis (TA) based on baseline rectal MRI for the early prediction of therapeutic response to neoadjuvant chemoradiotherapy (nCRT) and tumor recurrence in patients with locally advanced rectal cancer (LARC). Methods Consecutive patients with LARC who underwent rectal MRI between January 2014 and December 2015 and surgical resection after completing nCRT were retrospectively enrolled. Imaging features were analyzed, and TA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Interestingly, the largest majority of the published MRI radiomics studies takes into account histogram features (considered alone or in more advanced models based also on textural, shape, and filtered ones), supporting systematic investigations in this direction [ 28 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 ].…”
Section: Resultsmentioning
confidence: 67%
“…Interestingly, the largest majority of the published MRI radiomics studies takes into account histogram features (considered alone or in more advanced models based also on textural, shape, and filtered ones), supporting systematic investigations in this direction [ 28 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 ].…”
Section: Resultsmentioning
confidence: 67%
“…The intensity histogram feature of X0.975Quantile shows good repeatability in our study, which is similar to that in the reported research. [ 33 ] Shape features of Volume, Max3DDiameter, and Roundness provide the external morphologic features about the contours of the tumor. Our study illustrates the CECT radiomics model performs well in both the training group and the validation group, with AUC values of 0.815 and 0.720, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous results have been reported in different prediction models, referring to entropy, energy, and kurtosis. Two well-conducted studies reported that none of the T2WI radiomics features were significant predictors of response[ 35 , 36 ]. SVM, RF, and Naïve Bayesian network based on T2WI yielded promising results for complete response (CR) prediction [area under the receiver operating characteristic curve (AUC): 0.71-0.87][ 35 , 37 , 38 ].…”
Section: Radiomics Applications In Rcmentioning
confidence: 99%